Crocheting for dummies ebook - Brittain, Susan (Dummies., 2010)
An updated classic covering the latest techniques and trends in crocheting Are you hooked on the art of crochet? Looking for a fun new hobby that you can take with you virtually anywhere? Crocheting For Dummies, 2nd Edition gives you easy-to-understand instructions on how to choose the right tools, create basic stitches, and finish off your work to make beautiful pieces of art. From learning to create consistency with gauge swatch to decoding crochet patterns, symbols, and diagrams, this easy-to-follow guide is all you need to start creating beautiful designs in no time! This revised edition contains completely new content, including fresh new patterns, stitches, and techniques reflecting crocheting styles from around the world. Plus, it's packed with new and refreshed photos and line art throughout, along with step-by-step instructions that will easily guide you from your first stitch to your first sweater. A new section covering common crocheting mistakes and how to correct them Crocheting with eco-awareness: using organic yarns, as well as free trade and sustainably sourced fibers The best resources for purchasing supplies, as well as choosing and buying patterns Whether you're a first-time crocheter or looking to expand your skills, Crocheting For Dummies, 2nd Edition gives you the skills, techniques, and confidence to crochet like a pro. The EPUB format of this title may not be compatible for use on all handheld devices.